‘Modularization, standardization and actual combat’ of high-altitude military medical geography in a comprehensive military medical exercise - Chen, Yu; Chen, X; Tang, C; Liu, X; Luo, Y (BMJ military health, 2020)
Correspondence to Dr Y Luo, Department of Military Medical Geography, Army Health Service Training Base, Third Military Medical University, Chongqing, China; luo.yongjun@qq.com Dear editor, Soldiers have to face different environments according to different tasks, such as high-altitude, tropical, island and cold regions, as well as the Gobi Desert. [...]it is necessary to consider the impact of environmental characteristics on medical service, including the composition of casualties, the transportation and treatment of wounded and sick subjects, and the launching of rescue facilities. Continuing education in medicine: meeting service needs by improving the effectiveness of medical sergeants' training in 'high altitude sickness treatment and prevention'. Medical continuing education: reform of teaching methods about high altitude disease in China.